Invasive Aspergillus infection requiring lobectomy in a CYP2C19 rapid metabolizer with subtherapeutic voriconazole concentrations. (May 2016) - Hicks, J Kevin; Gonzalez, Blanca E; Zembillas, Anthony S; Kusick, Karissa; Murthy, Sudish; Raja, Siva; Gordon, Steven M; Hanna, Rabi
Individuals who carry the CYP2C19*17 gain-of-function allele have lower voriconazole exposure and are therefore at risk of failing therapy. Utilizing CYP2C19 genotype to optimize voriconazole dosage may be a cost-effective method of improving treatment outcomes. However, there are limited data describing what initial voriconazole dosage should be used in those with increased CYP2C19 metabolic capacity. Herein, we present a case report of a pediatric CYP2C19 rapid metabolizer (i.e., CYP2C19*1/*17 ) requiring a voriconazole dosage of 14 mg/kg twice daily (usual pediatric dosage ranges from 7 to 9 mg/kg twice daily). This case report supports the clinical utility of using CYP2C19 genotype to guide voriconazole dosing, and provides data for establishing an initial voriconazole dose in pediatric CYP2C19 rapid metabolizers.